Luxatio erecta humeri: Report of a swimming injury with analysis of the mechanism of the injury and associated injuries in literature - Kemal Gökkus; Ergin Sagtas; Murat Saylik; Ahmet Turan Aydin; Halil Atmaca (Journal of Emergencies, Trauma and Shock, 2015)
Inferior shoulder dislocation also referred to as luxatio erecta is an unusual and rare type of shoulder dislocation. Its incidence is about 0.5% among all shoulder dislocations. After an exhaustive search of all the available literature we were unable to find a swimming accident case that did not have other associated injuries and an uneventful reduction. The mechanism of the injury was mostly related to direct axial loading and indirect hyperabduction lever arm. We would like to emphasize the importance of this being a swimming accident, a type of accident that requires awareness of the possibility of dangerous asphyxia injuries caused by panic in the water (swimming pool, river, lake, sea, etc.). We described the nature of the injury and review the literature concerning the mechanism of the injury and associated neurovascular impairment at admission time. We also presented a supplemental video to contribute to the education of young residents and orthopedic surgeons.